Full spectrum analytical channel design with the capacity/supply ratio (CSR) - Stroth, Travis R., author; Bledsoe, Brian P., advisor; Nelson, Peter A., committee member; Rathburn, Sara L., committee member (Colorado State University. Libraries, 2017)
Analytical channel design tools have not advanced appreciably in the last decades, and continue to produce designs based upon a single representative discharge that may not lead to sediment continuity. It is beneficial for designers to know when a simplified design may be problematic and to efficiently produce alternative designs that approximate sediment balance over the entire flow regime. The Capacity/Supply Ratio (CSR) approach, an extension of the Copeland method of analytical channel design for sand channels, balances the sediment transport capacity of a design reach with the sediment supply of a stable upstream reach over the entire flow duration curve (FDC) rather than just a single discharge. Although CSR has a stronger physical basis than previous analytical channel design approaches, it has not been adopted in practice because it can be a cumbersome and time-consuming iterative analysis without the use of software. I present a novel design tool that was developed using the Visual Basic for Applications (VBA) programming language in Excel® and produces stable channel slope/width combinations based on the CSR methodology for both sand- and gravel-bed streams. The CSR Stable Channel Design Tool's (CSR Tool) code structure was based on Copeland's method in SAM and HEC-RAS (Hydrologic Engineering Center – River Analysis System) and was tested with a single discharge to verify outputs. Eighteen sand-bed rivers were investigated with the tool in a comparison of designs based on the CSR approach and five single-discharge metrics: the effective discharge (Qeff) or discharge that transports the most sediment over time, the 1.5-year recurrence interval discharge (Q1.5), bankfull discharge (Qbf), and the discharges associated with 50th (Qs50) and 75th (Qs75) percentiles of the cumulative sediment yield curve. The Qs50 and Qs75 single-discharge designs match the CSR output most closely followed by the Qbf and Qeff. The Qeff proved to be the most inconsistent design metric because it can be highly dependent on the binning procedure used in the effectiveness analysis. Furthermore, I found that the more rigorous physical basis of the CSR analysis is potentially most important in designing "labile' channels with highly erodible substrate, high perennial flow "flashiness', low width-to-depth ratio, and high incoming sediment load. The CSR Tool provides a resource for river-restoration practitioners to utilize process-based design techniques that can promote more reliable and sustainable designs for dynamic fluvial systems.
Keywords: capacity/supply ratio (CSR); stream restoration; sediment transport; analytical channel design